Transcriptomic Response to Feeding and Starvation in a Herbivorous Dinoflagellate - Rubin, Ewelina T.; Cheng, Shu; Montalbano, Amanda L.; Menden-Deuer, Susanne; Rynearson, Tatiana A. (Frontiers in Marine Science, 2019)
Grazing by heterotrophic protists influences plankton population dynamics, community composition, and the flux of carbon through marine planktonic food webs. To gain insight into the molecular underpinnings of grazing in dinoflagellates, a group of important heterotrophic protists, we used a RNA-Seq approach to investigate the transcriptomic response of Oxyrrhis marina under fed and starved conditions with three different phytoplankton prey (Isochrysis galbana and two strains of Heterosigma akashiwo). In response to fed and starved conditions, 1,576 transcripts were significantly differentially expressed in O. marina. Fed O. marina cells upregulated transcripts involved in the synthesis of essential fatty acids and storage carbohydrates suggesting that the predator was food satiated and excess glucose was being stored as an energy reserve. Transcripts encoding voltage-gated ion channels were also upregulated during grazing, and they are known to be involved in the detection of mechanical stimuli and the regulation of swimming behavior in several eukaryotic protists. Fed O. marina cells upregulated kinases, which can dictate cell shape changes and may be associated with phagocytosis. During starvation, upregulated O. marina transcripts included those involved in the degradation of energy-storage molecules like glucan 1,4-alpha-glycosidase and those involved in antioxidant activities and autophagy, like acid ceramidase that are associated with the digestion of polar lipids present in cell membranes. Starved O. marina also upregulated transcripts with high similarity to proton pumping proteorhodopsins suggesting that this heterotrophic protist may supplement its energy requirement during starvation with a light harvesting mechanism. Although herbivorous grazing is a pivotal transformation in the C cycle, logistical constraints limit our investigations of environmental and biological drivers. The molecular signals identified here provide new insights into the metabolic regulation of feeding and starvation in marine heterotrophic protists and can fuel hypothesis-driven research into predators’ metabolic response to prey availability.